Cathode plasma electrolytic deposition of Al2O3 coatings doped with SiC particles. Issue 4 (March 2019) - Liu, Chenxu; Zhang, Shuguang; Ji, Ruonan; Wang, Peng; Zhang, Jin; Tian, Yu; Meng, Yonggang; He, Yedong
Abstract: Semiconductor particles doped Al2 O3 coatings were prepared by cathode plasma electrolytic deposition in Al(NO3 )3 electrolyte dispersed with SiC micro- and nano-particles (average particle sizes of 0.5–1.7 µm and 40 nm respectively). The effects of the concentrations and particle sizes of the SiC on the microstructures and tribological performances of the composite coatings were studied. In comparison with the case of dispersing with SiC microparticles, the dispersion of SiC nanoparticles in the coatings was more uniform. When the concentration of SiC nanoparticles was 5 g/L, the surface roughness of the composite coating was reduced by 63%, compared with that of the unmodified coating. Friction results demonstrated that the addition of 5 g/L SiC nanoparticles reduced the friction coefficient from 0.60 to 0.38 and decreased the wear volume under dry friction. The current density and bath voltage were measured to analyze the effects of SiC particles on the deposition process. The results showed that the SiC particles could alter the electrical behavior of the coatings during the deposition process, weaken the bombardment of the plasma, and improve the structures of the coatings.